Measuring the gender disparities in unemployment dynamics during the recession evidence from Portugal - Passinhas, Joana (2022)
This article researches gender differences in the incidence and persistence of unemployment during the debt crisis and recession in Portugal through estimating a dynamic random effects probit model to control for unobserved individual heterogeneity and for the ‘initial conditions’ problem. The estimation applies data from four waves of ICOR – the Survey on Income and Living Conditions between 2010 and 2013. We find strong evidence of persistence in unemployment alongside indications that men are more prone to enduring negative implications from previous periods of unemployment. Simultaneously, we find evidence of a greater likelihood of unemployment for women through a fixed effect designed to capture gender discrimination in unstable labour markets. Our results suggest that policies to boost employment should accommodate a gender dimension and also place a special emphasis on the long-term unemployed